العتبات النصّيّة في مجموعة "عناقيد الزبد" للشّاعر "وفيق سليطين" - بَرهم لطفيّة; عطية قصي (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
يشتغل هذا البحث على "العتبات النصّيّة" في مجموعة "عناقيد الزبد" للشّاعر "وفيق سليطين"، التي تعدّ إشاراتٍ دالّةً تساعد المتلقّي في استكشاف ما تنطوي عليه نصوص المجموعة من معانٍ ودلالات. ويدرس البحث علاقةَ العنوان الخارجيّ بالعناوين الفرعيّة، وبالمتن النصّيّ؛ للوصول إلى الدلالات التشابكيّة القائمة بين العناوين والنّصوص داخل المجموعة الشّعريّة. This research sets light on the "Seuils" in the collection of "AnakeedAzzabad" for the poet "wafekSolaiton", which is considered guiding marks, that help reader to find out what meanings and signs which the collections contains. This research studies the connection between the main and secondary titles, and join it with the relation of the texts, to reach the interaction relation between texts inside collection.